MORPHOLOGICAL MEANS OF EXPRESSING THE RELATIONSHIP OF ANALOGY (Scientific journal of the Fergana State University, 2023)
In this article, linguistic means of representation and their formation as a whole system play an important role in the rapid and easy delivery of ideas, expressiveness of thought, involving different units and means of expression of language and speech. thought about the behavior. The range of linguistic means of expressing language analogy is somewhat broad, and this article presents ideas through the method of comparison.The formal indicators of simulation serve to create a new word in the simulation device, to give additional meaning, to perform the function of a part of speech. In this process, the various units and means of expression of language and speech play an important role in the imagery, effectiveness, quick and easy delivery of ideas.